A review on solar assisted heat pump systems in Singapore - Amin , Zakaria Mohd.; Hawlader, Mohammad Nurul Alam (Elsevier, 2013)
A solar assisted heat pump is used for different applications, such as, water heating, drying and air conditioning. The unglazed evaporator- collector enables to absorb both solar energy and ambient energy due to low operating temperature. Three different systems are described: solar assisted heat pump system for hot water using an unglazed evaporator collector; solar assisted heat pump for hot water and drying, where evaporator collector and air collector are used; an integrated solar heat pump system making use of solar and ambient energy, and air-con waste heat. Unlike conventional collector, evaporator collector was found to have higher efficiency, 80 to 90%, and the coefficient of performance attained a value as high as 8.0. The integrated system leads to a reduction of global warming, as it uses solar energy, ambient energy and air-con waste heat.